Development of an Effective Counselor Personality Model Rooted in Malay Culture - Mardes, Siska; Hayati, Isnaria Rizki; Rahman, Fadhila (Educational Guidance and Counseling Development Journal, 2025)
Culture influences every aspect of human life, including counseling practices. Cultural differences between counselors and clients can present challenges when counselors interpret clients' behavior through the lens of different cultural backgrounds. In the context of Indonesia, Western counseling theories are often used as references, although these cultural values do not always align with local wisdom. This study aims to explore the application of Malay culture as a model for effective counselor personality within a multicultural perspective. The research employs a literature review method by analyzing various sources related to counseling theories, Malay cultural values, and counselor competencies. The findings highlight that Malay-based counselors emphasize spirituality, knowledge, modesty, goodwill, and compassion. These values are rooted in tradition and local wisdom, prioritizing social relationships and human interconnectedness. An effective counselor not only possesses technical competence but also demonstrates empathy, patience, and high moral integrity. The results of this study emphasize the importance of developing a counseling model aligned with Indonesia’s local culture to make counseling services more relevant and effective. Malay culture, particularly in Riau Province, can serve as a reference in formulating an effective counselor’s personality. Adapting counseling approaches to local cultures is expected to enhance the quality and effectiveness of counseling services.